The Regulation of microRNAs in Alzheimer's Disease - Kou, Xianjuan; Chen, Dandan; Chen, Ning (Frontiers in Neurology, 2020)
MicroRNAs are small non-coding nucleic acids that are responsible for post-transcriptional gene silencing by binding to the coding region and 3’ and 5’ untranslated region of target messenger RNA. It has been estimated that approximately 70% of known microRNAs are expressed in the brain and increasing evidences demonstrate the possible involvement of microRNAs in Alzheimer’s disease (AD). The characteristic symptoms are the progressive loss of memory and cognitive functions due to the deposition of amyloid β (Aβ) peptide, intracellular aggregation of hyperphosphorylated Tau protein, the loss of synapses, and neuroinflammation, as well as dysfunctional autophagy. Therefore, microRNA-mediated regulation for above-mentioned changes may be the potential therapeutic strategies for AD. In this review, the role of specific microRNAs involved in AD and corresponding applications are systematically discussed, including positive effects associated with the reduction of Aβ or Tau protein, the protection of synapses, the inhibition of neruoinflammation, the mitigation of aging, and the induction of autophagy in AD. It will be beneficial to develop effective targets for establishing a direct link between pharmacological intervention and AD in the near future.